(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The paper examined the effectiveness of National Directorate of Employment (NDE) training strategy on cluster of business linkages and domestic investment towards poverty reduction. Two research questions guided the study. The population consisted of 47,298 beneficiaries of NDE training in Oyo State, total of 4,729 respondents were selected through stratified sampling technique. The study adopted survey design. A four point structured questionnaire was used for data collection. The instrument was validated by four experts. An internal consistency of 0.80 was obtained using Croncbach Alpha correlation co-efficient. Mean and standard deviation were used to answer the research questions. The study showed that the cluster of business linkages and domestic investment training strategies of NDE were effective. It was concluded that NDE training strategies reduced unemployment problems in Oyo State. It was recommended among others that linkages, networking, collaboration and association should take priority in the NDE training and that the NDE should continue its training ondomestic investment.